SLEEP HEALTH AND FUNCTIONAL LIMITATIONS IN OLDER ADULTS. (11th November 2018) - Stone, K L; Blackwell, T; Ancoli-Israel, S; Ensrud, K E; Kado, D M; Wallace, M L; Cawthon, P M; Buysse, D J
Abstract: Individual sleep symptoms are associated with a variety of age-related outcomes, yet few studies have considered how multidimensional sleep symptoms relate to health outcomes. We examined both individual and multiple dimensions of sleep in relation to prevalent and incident functional limitations in 3610 older women and 3111 older men. Individual dimensions of self-reported sleep health included sleep satisfaction, daytime sleepiness, mid-sleep timing, sleep onset latency, and sleep duration. An aggregate index (0 to 5) was created. Outcomes included prevalent impairment in Independent Activities of Daily Living (IADL) and incident functional limitations (≥ 1 IADL at follow-up among those with none at baseline) over 3–5 years. In both sexes, poor sleep health was associated with greater odds of prevalent disability. Although women were more likely to report multiple sleep health problems, these problems increased the risk of incident disability only among men. Further investigation of the observed sex differences is warranted.